A Data Literate Ireland: The Case for a Whole-of-Government Approach to Data Literacy Skills Development in Ireland - Darling, Orlaith; Hurley, Mairéad; Grehan, Laura; Kearns, Anne (My University, 2022)
Data literacy is broadly defined as “the ability to read, work with, analyse, and argue with data.” The Open Data Institute highlights that data literacy goes beyond the technical skills of working with data, emphasising the need to think critically about data and its presentation in different contexts. In 2018, The Council of the European Union adopted a recommendation on eight key competences for lifelong learning. The recommendation states that these are essential to citizens for personal fulfilment, a healthy and sustainable lifestyle, employability, active citizenship and social inclusion. Digital competence is one of these key competences. The European’s Commission’s Digital Competence Framework for Citizens (DigComp 2.0) states that “Digital skills for work and for life are at the top of the European Policy Agenda”. The framework highlights that due to emerging technologies, such as Artificial Intelligence, Virtual and Augmented Reality, robotisation, the Internet of Things, datafication, or phenomena such as misinformation and disinformation, there are now new and increased digital literacy requirements on the part of the citizen. ‘Information and Data Literacy’ has been identified as the first of five competence areas to increase digital competence. It is ADAPT’s position that there must be a blended, joined-up approach to improving digital literacy across Irish society. This issue is not the responsibility of one government department or agency; instead a whole-of-government approach, one that is cross- institute and cross-discipline - must be taken to solve this complex problem. These conclusions are in line with those reached by the Department of Enterprise, Trade and Employment (DETE), the National Skills Council (NSC), the National Adult Literacy Agency (NALA), and the Government of Ireland’s Adult Literacy for Life (ALL) report that AI and digital literacy skills are embedded. Just as DETE, NSC, NALA and ALL conclude that AI and digital literacy skills are embedded alongside the need for lifelong learning and adult literacy skills in Ireland, we need to ensure that data literacy is included in this broad understanding of “digital literacy” and take a whole-of-government approach to data literacy skills development in Ireland. In this document ADAPT provides a definition of data literacy, assesses the current landscape around education and training in data literacy available for the Irish public, summarises findings from a pilot scheme ADAPT has created to increase data literacy skills in hard-to-reach communities, and proposes how to upscale these findings into a recommendations for a whole-of-government approach to data literacy skills development in Ireland. Data Literacy: A Key 21st Century Skill According to the European Commission, data literacy – the ability to locate, judge the relevance of, and organise data – is liked to a range of key competences for modern life including engaged citizenship, “netiquette”, and operating safely and securely online. The National Adult Literacy Agency (NALA) states that “literacy is a barometer of equality”. While NALA does not mention data literacy specifically, it notes that “literacy enables us to be critically reflective and engaged citizens, which is essential in today’s news, media and digital world.”⁶ It is clear that data literacy is now an essential life skill for citizens, workers, and people of all ages and demographics. Data Literacy Further Education and Training: The Current Landscape In July 2021, the Irish Government, in collaboration with SOLAS (the Irish state agency for Further Education and Training), published ‘Adult Literacy for Life (ALL), A 10-Year Adult Literacy, Numeracy and Digital Literacy Strategy’. This strategy represents a reorientation of adult literacy education and training provision from a piecemeal pursuit to a joined-up “whole-of-government approach for investing in adult literacy, numeracy and digital skills for an equal and resilient Ireland.” ALL lists digital, family, environmental, financial, health, media and numeric literacy as key competences. However, there is no specific mention of data literacy. By contrast, the European Commission’s Digital Competence Framework, DigComp¹⁰, which provides a basis for framing digital skills policy, lists Information and Data Literacy as one of five competence areas required for 21st Century citizens. ADAPT believes that it would represent a substantial missed opportunity for Ireland if data literacy were not included in the rollout of the systems-based approach to further education and training provision in adult literacy, numeracy and digital literacy espoused by Adult Literacy for Life (ALL). Debunked: Learnings from Informal Data Literacy Workshops This paper purports that greater levels of data literacy are required in Ireland. While industry, schools and higher education institutions are being equipped to deliver this in their respective spheres, there remain many citizens outside this remit. ADAPT, the Science Foundation Ireland Research Centre for AI-Driven Digital Content Technology, worked with one such group in a series of data literacy workshops in 2021, delivering “Debunked”: a pilot-scale series aimed at local residents in Dublin’s Grand Canal Dock District. Debunked identified four approaches to overcome the challenges of delivering effective data literacy training, which also broadly aligned with research laid out by the Partnership in Statistics for Development in the 21st Century (Paris21) on how to successfully advance data literacy after the pandemic.
PUBLISHED
Keywords: Digital Engagement